Mastering CentOS 7 Linux server : configure, manage, and secure a CentOS 7 Linux server to serve a variety of services provided in a sustainable computer's infrastructure - Alibi, Mohamed; Roy, Bhaskarjyoti (Community experience distilled., 2016)
Annotation